1992
DOI: 10.1029/92gl02178
|View full text |Cite
|
Sign up to set email alerts
|

Pressure gradient structures in the tail neutral sheet as “roots of the arcs” with some effects of stochasticity

Abstract: Westward cross‐tail current at the earthward edge of the plasma sheet is enhanced due to strongly stochastic (rLi ∼ Rc) ion motions. A narrow elongated magnetic field depression arises which leads to further stochastication of the ions convecting through it, and to a local increase of magnetostatic plasma pressure, enhanced lateral transport and removal of higher energy ions. This plasma structure can be stationary in the magnetospheric frame. It is the “root” of sheet‐like auroral currents of stable auroral h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 15 publications
3
32
0
Order By: Relevance
“…A comparison between the wave phase and the derivative of DC B Y component is consistent with the field variations produced by a DC current modulation. A second increase of the wave power started around 18:01:05 UT (when EQUB was (Lu et al, 1991;Galperin et al, 1992); d resulting Pedersen conductivity identified) with the maximum of power density registered at the higher frequency. For this band the wave phase-DC B Y correlation is not so good as for the POLB.…”
Section: Multiple Current Sheets On Pass 1563 Of the Magion-2mentioning
confidence: 99%
See 3 more Smart Citations
“…A comparison between the wave phase and the derivative of DC B Y component is consistent with the field variations produced by a DC current modulation. A second increase of the wave power started around 18:01:05 UT (when EQUB was (Lu et al, 1991;Galperin et al, 1992); d resulting Pedersen conductivity identified) with the maximum of power density registered at the higher frequency. For this band the wave phase-DC B Y correlation is not so good as for the POLB.…”
Section: Multiple Current Sheets On Pass 1563 Of the Magion-2mentioning
confidence: 99%
“…4. a Magnetic field components in the EQUB's principal axis reference system; b field aligned current density (positive for downward current); c resulting field aligned potential drop (Lu et al 1991;Galperin et al, 1992); d resulting Pedersen conductivity 6 Inferred and observable auroral and precipitation effects…”
Section: Multiple Current Sheets On Pass 2057 Of the Magion-3mentioning
confidence: 99%
See 2 more Smart Citations
“…Pressure gradients have been discussed in connection to auroral arc formation, e.g. by Galperin et al (1992).…”
Section: Recent Observations Confirm Earlier Studiesmentioning
confidence: 99%